Non-Cyclical Fluctuations in GDP Growth in Poland - Sztaudynger, Jan Marek (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The aim of the study presented in the paper is to verify the hypothesis of non cyclical economic fluctuations; in particular, the hypothesis concerning the irregularity of causes and the hypothesis concerning the regularity of rebalancing the economy. Slow past GDP growth is taken as a symptom of disequilibrium, that is, the occurrence of either fixed asset bottlenecks or demand shortages. These two causes of disequilibrium arise irregularly in the economy. The hypothesis tested states that the slower the economic growth that occurred in the past, the stronger the compensatory GDP growth that will occur in the future. This is the regularity of rebalancing. The method of least squares was used to estimate a modified Solow model for Poland’s GDP in the years 1994–2019. The most important modification consisted in replacing the dynamics of net physical capital, which is not available in Polish statistics, with the investment rate. The second reason for this modification is the inaccuracy of statistical data on gross physical capital, which cannot be avoided. Another modification was the introduction of lagged GDP growth into the model as an indicator of disequilibrium. The hypothesis that the intensified occurrence of bottlenecks results in greater investment efficiency after 3–5 years has been confirmed. On the other hand, a slowdown in GDP growth results after 1–2 years in the accumulation of unused capacity, which enables a compensatory acceleration of economic growth. Thus, the hypothesis of the occurrence of non cyclical economic fluctuations in the Polish economy has been confirmed.